2002
DOI: 10.1029/2001ja000325
|View full text |Cite
|
Sign up to set email alerts
|

Energetic neutral atoms at Mars 1. Imaging of solar wind protons

Abstract: [1] Energetic neutral atom (ENA) images are computed from an empirical solar wind proton model and recent models of the Martian exosphere. The proton model describes the proton bulk velocity in the interaction region and the neutral model the profiles of H, H 2 and O (hot) and O (thermal). We assume a Maxwellian proton velocity distribution. The ENA production model is analytical; thus an ENA image can be constructed for any vantage point by line of sight integration, and we present examples of such images. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 24 publications
1
53
0
1
Order By: Relevance
“…Recent observations revealed that the solar wind protons can penetrate up to 270 km ], and this means that this proton-ENA albedo mechanism can be more important than expected. This mechanism is mentioned by Holmström et al (2002). They used a proton precipitation flux of 10 4 -10 5 cm −2 s −1 [Brecht (1997)] and concluded that the proton-ENA albedo mechanism can be negligible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent observations revealed that the solar wind protons can penetrate up to 270 km ], and this means that this proton-ENA albedo mechanism can be more important than expected. This mechanism is mentioned by Holmström et al (2002). They used a proton precipitation flux of 10 4 -10 5 cm −2 s −1 [Brecht (1997)] and concluded that the proton-ENA albedo mechanism can be negligible.…”
Section: Discussionmentioning
confidence: 99%
“…We call this mechanism 'proton-ENA albedo process' hereafter. The ENA flux generated by this proton-ENA albedo process was mentioned by Holmström et al (2002). They used the proton precipitation flux calculated by Brecht (1997), and concluded that the flux of ENAs associatively produced is small enough to be neglected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a more detailed description of the generation of ENA images [see, e.g., Holmström et al, 2002]. To exclude other ENAs than of solar wind origin in our simulations we use a cometopause as an inner boundary-separating the solar wind dominated outer region and the inner region dominated by cometary ions-at 1.8 Á 10 8 m. This value was chosen as the distance where 10% of the solar wind density would be depleted if using a constant solar wind density and velocity in equation (2).…”
Section: Ena Production Modelmentioning
confidence: 99%
“…ENA albedo is produced when charge-exchange ENAs are generated above the Induced Magnetosphere Boundary (IMB; Lundin et al, 2004), cross the IMB and are back-scattered against the exobase (Kallio and Barabash, 2001). A fraction of SW protons cross the IMB due to finite Larmor radius effect and experience a back-scattering process (proton-ENA albedo, Holmström et al, 2002), thereby potentially contributing to the overall signal. In addition, spatially constrained and highly directional ENA fluxes (ENA jets) up to 7×10 5 cm -2 sr -1 s -1 , in the 0.3-3 keV energy range, emanating from a compact region of the sub-solar exosphere, have been detected by the NPD (Futaana et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%